THE EFFECT OF IRON CONTENT ON THE PHASE TRANSFORMATION OF TIO2 NANOCRISTALLINE POWDERS PREPARED BY SOL GEL PROCESS (Sciences & Technology. A, exactes sciences, 2010)
Pure and Fe3+ - doped TiO2 nanoparticles were prepared by sol–gel method, using TiCl4 and FeCl3 as starting materials, ethanol as a solvent and ammonium hydroxide as a catalyst. The structural, morphological and optical properties of as prepared powders were investigated by X-ray diffraction, scanning electron microscopy and UVvisible absorption spectroscopy. The quality of the samples was examined by Infra-red absorption spectroscopy and room temperature photoluminescence (PL). All samples shows anatase phase except the 0.1 mol % Fe3+ - doped TiO2 sample, which rutile phase was appeared. The particle sizes decrease when the iron content increases.From SEM images, the morphology and size of particles were affected by amount of doped metal. The absorption edge of Fe3+ - doped TiO2 shifted towards visible spectrum when the Fe3+ - doped concentration increased. from the infra-red absorption spectra, the materials showed a highly pure and strongly surface hydrated, the materials shows main PL emission peaks appears in UV, and visible regions.